2015
DOI: 10.1016/j.ijggc.2015.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Passive acoustic quantification of gas fluxes during controlled gas release experiments

Abstract: 10The detection and quantification of an underwater gas release is becoming increasingly

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 57 publications
0
40
0
1
Order By: Relevance
“…The interpretation of multiple mechanisms supports also the analysis of ocean tides on the SDE occurrence. Tidal modulation of gas discharge from gas reservoirs is well documented in a variety of environments (e.g., Algar et al, ; Bergès et al, ; Boles et al, ; Torres et al, ) where intensified gas release was observed during periods of low tide. Thus, missing clear effect of tides on the SDEs occurrence at the MASOX site (Figures b and c) indicate that besides gas seepage‐related source mechanism of the SDEs another mechanism that is weakly influenced by tides is involved and perhaps more efficient in generating SDEs.…”
Section: Discussionmentioning
confidence: 99%
“…The interpretation of multiple mechanisms supports also the analysis of ocean tides on the SDE occurrence. Tidal modulation of gas discharge from gas reservoirs is well documented in a variety of environments (e.g., Algar et al, ; Bergès et al, ; Boles et al, ; Torres et al, ) where intensified gas release was observed during periods of low tide. Thus, missing clear effect of tides on the SDEs occurrence at the MASOX site (Figures b and c) indicate that besides gas seepage‐related source mechanism of the SDEs another mechanism that is weakly influenced by tides is involved and perhaps more efficient in generating SDEs.…”
Section: Discussionmentioning
confidence: 99%
“…Timescales for emissions vary widely from observational, through daily, to seasonal (Bergès, Leighton, and White 2015, Kretschmer et al 2015, Leifer and Judd 2015. Timescales for emissions vary widely from observational, through daily, to seasonal (Bergès, Leighton, and White 2015, Kretschmer et al 2015, Leifer and Judd 2015.…”
Section: Trap Integrity and Leaksmentioning
confidence: 99%
“…A key issue with CCS is ensuring that sequestered gas remains in the sub-surface, and that any significant leakage is detectable. In the marine environment there has been experimentation to determine the limits for this detection, as well as localization and quantification of CO 2 leakage from controlled subseabed gas release experiments [8,9,10,11,12,13]. With regard to quantifying gas leakage using acoustic techniques, ambient noise is an essential factor that needs to be considered [14].…”
Section: Introductionmentioning
confidence: 99%